Compressive behavior of concrete-filled steel tubular columns with internal high-strength steel spiral confinement. Issue 8 (June 2021) - Teng, J.G.; Wang, J.J.; Lin, Guan; Zhang, J.; Feng, P.
Concrete-filled steel tubular (CFST) columns have been extensively studied and widely used in practice. Existing research has shown that non-circular CFST columns is much less ductile than their circular counterparts, particularly when thin/high strength steel (HSS) tubes and high-strength concrete are used. To address this problem, a new form of CFST columns has recently been proposed by the first author. The new column consists of a steel tube filled with concrete that is confined with HSS spiral reinforcement typically with a yield stress exceeding 1000 MPa. These columns, referred to as confined concrete-filled steel tubular (CCFST) columns, also maintain the ease for connection to CFST or steel beams. This paper presents the results of a series of concentric axial compression tests on such columns of square cross-section to demonstrate their advantages. The experimental program included 13 CCFST columns, four CFST columns without internal spiral confinement, two hollow steel tube (HST) columns, and 11 circular HSS spiral-confined concrete columns. Three different compressive strengths and three HSS spiral pitches were examined in the experimental program. The CFST columns, HST columns, and HSS spiral-confined concrete columns were all tested under axial compression to gain a good understanding of the confinement mechanism in a CCFST column. The test results show that the new columns possess much greater ductility than those without internal spiral confinement, although the use of HSS spirals increases the steel volume by only a small percentage. It is also shown that the axial load-axial strain curve of a CCFST column can be conservatively predicted by summing the axial load-axial strain curves of the hollow steel tube without local buckling, the HSS spiral-confined concrete core, and the sandwiched concrete between the two.